Characterization of materials and their interfaces in a direct bonded copper substrate for power electronics applications. (December 2017) - Kabaar, A. Ben; Buttay, C.; Dezellus, O.; Estevez, R.; Gravouil, A.; Gremillard, L.
Abstract: Direct bonded copper (DBC) are produced by high temperature ( >1000 ° C) bonding between copper and a ceramic (usually alumina). They are commonly used in power electronics. However, their reliability when exposed to thermal cycling is still an issue, that could be addressed by advanced numerical simulations. This paper describes the identification of the parameters for a numerical model that uses finite elements with cohesive zones. This identification is based on careful mechanical characterization of all components of the DBC (ceramic, copper and interface) using an innovative approach based on image correlation. Highlights: Key components of a DBC Substrate are studied: copper, ceramic, and their interface. For each of them, a model is identified from experiments. Copper behaviour is strongly affected by annealing during assembly. Interface bonding is identified from both local and global measurements.